Synchrotron X‐Ray Tomography for Rechargeable Battery Research: Fundamentals, Setups and Applications. Issue 9 (3rd August 2021) - Tang, Fengcheng; Wu, Zhibin; Yang, Chao; Osenberg, Markus; Hilger, André; Dong, Kang; Markötter, Henning; Manke, Ingo; Sun, Fu; Chen, Libao; Cui, Guanglei
Abstract: Understanding the complicated interplay of the continuously evolving electrode materials in their inherent 3D states during the battery operating condition is of great importance for advancing rechargeable battery research. In this regard, the synchrotron X‐ray tomography technique, which enables non‐destructive, multi‐scale, and 3D imaging of a variety of electrode components before/during/after battery operation, becomes an essential tool to deepen this understanding. The past few years have witnessed an increasingly growing interest in applying this technique in battery research. Hence, it is time to not only summarize the already obtained battery‐related knowledge by using this technique, but also to present a fundamental elucidation of this technique to boost future studies in battery research. To this end, this review firstly introduces the fundamental principles and experimental setups of the synchrotron X‐ray tomography technique. After that, a user guide to its application in battery research and examples of its applications in research of various types of batteries are presented. The current review ends with a discussion of the future opportunities of this technique for next‐generation rechargeable batteries research. It is expected that this review can enhance the reader's understanding of the synchrotron X‐ray tomography technique and stimulate new ideas and opportunities in battery research. Abstract : The current review focuses on the application of the synchrotron X‐ray tomography technique in battery research. Firstly, fundamental principles and experimental setups of this technique are detailed. Secondly, a user guide to its application in battery research and an extensive case summary are presented. The review ends with the discussion of the future opportunities of this technique for next‐generation battery research.